PENGARUH BRAND EXTENSION TERHADAP CITRA MEREK DAN MINAT BELI PADA PRODUK NUTRISARI W’DANK DI KECAMATAN TAMPAN PEKANBARU - Nova Theresia Sitepu; Jushermi -; Taufiqurrahman - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is aimed to analyze the effect of Brand Extension towards Brand Image and Purchase Intention on Nutrisari W'dank product in Tampan district, Pekanbaru. Population of this research are consumers who lived in Tampan district and its respondents must be 14 years old or above who have ever consumed Nutrisari product. The method being used is area sampling with 100 respondents. Data are collected by giving questionaires to respondents. In terms of data analysis, this research uses path analysis by using spss version 17.0. The results of this research shows that Brand Extension and Brand Image affect both positively and significantly towards Purchase Intention on Nutrisari W’dank product in Tampan district, Pekanbaru. Moreover, Brand Extension is also affecting Brand Image significantly. On the context of direct impact, Brand Image gives higher effect than Brand Extension to Purchase Intention on Nutrisari W’dank product in Tampan district, Pekanbaru.Keywords: Brand Extension, Brand Image and Purchase Intention.